2021
DOI: 10.3390/ani11041011
|View full text |Cite
|
Sign up to set email alerts
|

Toxic and Microbiological Effects of Iron Oxide and Silver Nanoparticles as Additives on Extended Ram Semen

Abstract: The aim of the study was to investigate the effect of iron oxide (Fe) and silver (Ag) nanoparticles (NPs) on ram semen. A skim milk extender without antibiotics was used as a diluent of 21 ejaculates (8 rams; 2–3 ejaculates/ram). The groups of control (C; semen without NPs), Fe NPs (3.072 mg Fe3O4/mL semen), and Ag NPs (2.048 mg Ag-Fe/mL semen) were incubated (15 °C; 30 min), and then a magnetic field was used for NPs’ removal. Standard microbiological procedures were performed for all groups. Post-treated sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Combating hoof disorders in cows [50,51] Au-NPs Inorganic Bacillus anthracis Induce ROS to disrupt cell membrane.…”
Section: Inorganicmentioning
confidence: 99%
See 1 more Smart Citation
“…Combating hoof disorders in cows [50,51] Au-NPs Inorganic Bacillus anthracis Induce ROS to disrupt cell membrane.…”
Section: Inorganicmentioning
confidence: 99%
“…Moreover, Hasssan et al [49] reported that NMs, like ZnO, can improve animal health by promoting development and reducing diarrhea in piglets and dairy cows with recessive mastitis. Furthermore, Tsakmakidis et al [50] study on FeO and Ag-NPs on ram sperm found that Ag-NPs demonstrated superior antibacterial activity and cytotoxicity, indicating potential for sperm therapy. Accordingly, Kot et al [51] explored the effectiveness of metal NPs (Ag-NPs, Cu-NPs, Au-NPs, Pt-NPs, and Fe-NPs) in combating digital dermatitis in cows caused by Treponema bacteria, with Ag-NPs and Cu-NPs showing the most biocidal effect.…”
Section: Inorganic Nmsmentioning
confidence: 99%
“…A slight antibiotic effect with no detrimental effects on the sperm quality was observed when iron oxide nanoparticles were added [ 81 ]. The desired antibacterial effect was recorded when iron and silver nanoparticles were combined at the cost of increased spermatotoxicity [ 82 ]. Yousef et al [ 83 ] disclosed that concentrations ≤30 µg/mL of silver-carbon nanoparticles did not affect sperm quality parameters during bull semen storage and were effective against Staphylococcus aureus , Pseudomonas aeruginosa , and Escherichia coli , although transmission electron microscopy revealed that these nanoparticles were attached to the plasma membrane but did not penetrate the bull sperm cell.…”
Section: Antimicrobial Proteins Biocompounds Plant Extracts and Nanop...mentioning
confidence: 99%
“…Consequently, MACS application has improved pregnancy rates in comparison to spermatozoa processed by density gradient alone [153]. Non-thermal plasma has emerged as an alternative technique with exceptional potential in various biomedical directions including the sterilization and sanitation of different surfaces [114,121,125], wound healing [124,126], tissue regeneration [124,127], treatment of infections [127,128], and cancer [80][81][82]. In particular, interactions of NTP with both Grampositive and Gram-negative bacteria, biofilms, spores, and fungi have been extensively studied over the past decade [116,129,130].…”
Section: Magnetic-activated Cell Sortingmentioning
confidence: 99%
“…The addition of iron oxide (Fe 3 O 4 ) nanoparticles during boar semen processing was reported to produce a slight antibiotic effect with no adverse effects on sperm characteristics [64]. In contrast, although iron oxide nanoparticles were not toxic to ram spermatozoa, they did not have the desired antibacterial effect [65]. A combination of silver and iron oxide nanoparticles produced a greater antibacterial effect than iron oxide but showed higher spermatotoxicity.…”
Section: Nanoparticlesmentioning
confidence: 99%